Clinical application and development of OCT and OCTA in fundus diseases - Xu , Jingru (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Optical coherence tomography (OCT), which uses light wave as the imaging method, is a new medical imaging technology based on optical coherence. Optical coherence tomography angiography (OCTA) is a non-invasive imaging method gradually emerging in recent years. This technique can detect flowing blood and evaluate tissue morphology by detecting normal flow of red blood cells in blood vessels. Because of the advantages of high resolution, easy operation and three-dimensional imaging, it is widely used in the diagnosis and evaluation of fundus diseases (such as diabetic retinopathy, choroidal neovascularization, retinal vein occlusion, etc.). This article reviews the application status and progress of OCT and OCTA in clinical diagnosis and treatment of fundus diseases.